Oferta y consumo de contenidos televisivos transnacionales en México - José Carlos Lozano (Estudios sobre las Culturas Contemporáneas)
While the uneven flow of transnational media messages lias been widely studied and documented by a number of scholars in different parts of the world, there has been a scarcit)´ of more detailed studies about die kind of foreign supply and its reception tmd appropriation by different audiences in different countries. This paper reviews most of die recent studies done in Mexico about these two analytical axes iuid discusses the theoretical implications of their findings.